2014
DOI: 10.1126/scitranslmed.3008140
|View full text |Cite
|
Sign up to set email alerts
|

Potent Neutralization of MERS-CoV by Human Neutralizing Monoclonal Antibodies to the Viral Spike Glycoprotein

Abstract: The recently identified Middle East respiratory syndrome coronavirus (MERS-CoV) causes severe and fatal acute respiratory illness in humans. However, no prophylactic and therapeutic agents specifically against MERS-CoV are currently available. Entry of MERS-CoV into target cells depends on binding of the receptor binding domain (RBD) of the viral envelope spike glycoprotein to the cellular receptor dipeptidyl peptidase 4 (DPP4). We report the isolation and characterization of two potent human RBD-specific neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
232
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(236 citation statements)
references
References 49 publications
2
232
1
1
Order By: Relevance
“…For our studies, we selected a panel of three antibodies with published variable domain sequences, which were reported to potently neutralize MERS-CoV and bind to diverse epitopes. The published sequences for antibodies 3B12, MERS-4, and MERS-27 (27,32) were cloned onto human IgG1 constant domains, then expressed and purified similarly to REGN3051 and REGN3048. We tested the three purified antibodies for binding to MERS S protein, blockade of the S protein-DPP4 interaction, and published neutralization properties (Fig.…”
Section: Breadth Of Mers-cov Neutralization By Regn3051 and Regn3048mentioning
confidence: 99%
“…For our studies, we selected a panel of three antibodies with published variable domain sequences, which were reported to potently neutralize MERS-CoV and bind to diverse epitopes. The published sequences for antibodies 3B12, MERS-4, and MERS-27 (27,32) were cloned onto human IgG1 constant domains, then expressed and purified similarly to REGN3051 and REGN3048. We tested the three purified antibodies for binding to MERS S protein, blockade of the S protein-DPP4 interaction, and published neutralization properties (Fig.…”
Section: Breadth Of Mers-cov Neutralization By Regn3051 and Regn3048mentioning
confidence: 99%
“…With a yeast displayed scFv library and purified RBD as panning target, Jiang et al identified two antibodies (MERS-4 and MERS-27) that can neutralize MERS-CoV infection as well as inhibit syncytia formation [13]. These two mAbs bind to RBD with nanomolar binding affinities.…”
Section: Current Nabs Against Mers-covmentioning
confidence: 99%
“…Human monoclonal neutralising antibodies and convalescent sera from recovered patients might be useful for treatment if delivered in a timely fashion 91,101,102 , an exploratory post-hoc meta-analysis of studies of SARS and severe influenza showed a significant reduction of mortality following antibody treatment compared with placebo or no treatment 103 . Systemic corticosteroids have been used empirically in some patients to dampen immune pathological host responses, although no survival benefit has been reported 95 .…”
Section: Treatmentmentioning
confidence: 99%